The Physiological Role of BNP and Galectin-3 in Predicting Pacing Dependency in Patients with Cardiovascular Implantable Electronic Devices - Salih, Khalid Saud (Al-Rafidain Journal of Medical Sciences ( ISSN 2789-3219 ), 2025)
Background: Pacemaker dependency is a critical consideration in patients with cardiovascular implantable electronic devices (CIEDs). Objective: To evaluate the predictive value of B-type natriuretic peptide (BNP) and galectin-3 in forecasting pacing dependency in patients with CIED. Methods: One hundred patients with CIEDs were classified as pacing dependent (n=39) or non-dependent (n=61) based on established criteria. Associations with clinical and biomarker variables were analyzed using univariate and multivariate logistic regression. Receiver operating characteristic (ROC) curves assessed the predictive value of BNP and galectin-3. Results: Pacing dependency was significantly associated with longer CIED duration (≥5 years), chronic kidney disease, and second- or third-degree atrioventricular block. Patients with severe left ventricular dysfunction were more likely to be pacing dependent. Median BNP and galectin-3 levels were significantly higher in the pacing-dependent group (269pg/ml and 22ng/ml, respectively). Multivariate analysis identified CIED duration >5 years (OR=3.28), CKD (OR=3.47), NYHA class III (OR=3.88), NYHA class IV (OR=5.33), BNP >160pg/ml (OR=6.23), and galectin-3 >16ng/ml (OR=2.12) as independent predictors of pacing dependency. The ROC analysis showed that BNP (AUC=0.836) and galectin-3 (AUC=0.715) were good predictors, and they were even better when used together (AUC=0.912, sensitivity=87%, specificity=85%). Conclusions: BNP and galectin-3 are valuable biomarkers for predicting pacing dependency in patients with CIEDs, and they provide a robust model for identifying patients at higher risk of pacing dependency when combined with clinical parameters.